Low-emission polyolefin composite material as well as preparation method and application thereof
By using specific composite antioxidants and ethylene-1-octene block copolymers in polyolefin composites, the problem of odor emission in high temperatures or long-term use is solved, and better antioxidant and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411991899.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
During the high temperature or long-term use of existing polyolefin composite materials, physically adsorbed substances will still be emitted, endangering human health.
Using a specific combination of composite antioxidants and ethylene-1-octene block copolymer, the precipitation of small molecule additives and oxidation products is reduced by forming a stable crystalline network structure and optimizing the compatibility of antioxidants.
It significantly improves the oxidation resistance of polyolefin composite materials, reduces the odor emission performance, and maintains good mechanical properties.
Smart Images

Figure BDA0005223827120000071 
Figure BDA0005223827120000081 
Figure BDA0005223827120000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polypropylene compositions, and more specifically, relates to a low-emission polyolefin composite material and a preparation method and application thereof. Background Art
[0002] In the automotive and construction industries, higher requirements are placed on the emission of harmful substances (such as formaldehyde, VOC, haze) and odor inside automobiles and building spaces. The odor of polyolefins is related to the precipitation and dissolution of additives, as well as the oxidative degradation of polyolefins themselves.
[0003] At present, the following measures are mainly used to reduce odor: 1. Replace the additives that emit unpleasant odor with low-odor substitutes; 2. Use purer resins; 3. Add adsorbents, including physical adsorption and chemical reaction methods. Among them, the third method is currently the most widely used method.
[0004] Physical adsorption refers to the use of porous materials with high specific surface area to adsorb volatile small molecules. With the continuous development of the physical adsorbent industry, there are many types of physical adsorption systems. Including activated carbon, silica gel, attapulgite, clay mineral system, molecular sieve, zeolite, expanded soil, etc. When they are evenly dispersed in the resin system, they can adsorb small molecules with pore sizes smaller than their own micropores, thereby reducing odor. Physical adsorption can have a good effect at room temperature in the short term, but because adsorption and removal is a reversible process, the physically adsorbed substances will still be emitted during high temperature or long-term use, which is harmful to human health.
[0005] Therefore, how to develop a polyolefin composite material that still has low odor during high temperature or long-term use has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing polyolefin composite materials that physically adsorbed substances will still be emitted during high temperature or long-term use, which is harmful to human health, and to provide a low-emission polyolefin composite material.
[0007] The purpose of the present invention is to provide a method for preparing the low-emission polyolefin composite material.
[0008] Another object of the present invention is to provide application of the low-emission polyolefin composite material.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] The present invention protects a low-emission polyolefin composite material, which comprises the following components by weight: 70 to 85 parts of polypropylene, 15 to 30 parts of ethylene-1-octene block copolymer, 1 to 6 parts of a compatibilizer, 0.1 to 1 part of a composite antioxidant, and 0 to 55 parts of a filler; wherein the composite antioxidant comprises an amine antioxidant and a hindered phenol antioxidant.
[0011] The above-mentioned specifically matched composite antioxidant has good antioxidant performance in the polyolefin composite material system described in the present invention; in addition, on the one hand, the hard segment of the ethylene-1-octene block copolymer has a higher crystallization rate and a more regular crystal morphology, and can work together with the polypropylene matrix to obtain a stable crystal network structure, hindering the precipitation of small molecule additives and oxidation products; on the other hand, the ethylene-1-octene block copolymer has good processing performance, and its soft segment has good compatibility with the amine antioxidant, further reducing the precipitation of the antioxidant, so that the composite antioxidant can play a good synergistic role, long-term guarantee The antioxidant performance of the polyolefin composite material, fundamentally reduce the oxidative degradation of the polyolefin composite material, and reduce the odor emission performance of the polyolefin composite material; and the resulting low-emission polyolefin composite material also has good mechanical properties.
[0012] Furthermore, the amine antioxidant includes at least one of an aromatic amine antioxidant and an alkyl diphenylamine antioxidant.
[0013] Preferably, the aromatic amine antioxidant includes at least one of diphenylamine and p-phenylenediamine.
[0014] Preferably, the alkyl diphenylamine antioxidant includes at least one of octylated diphenylamine, 4,4'-di(phenylisopropyl)diphenylamine, octyl diphenylamine, nonyl diphenylamine, and styryl diphenylamine.
[0015] Furthermore, the hindered phenol antioxidant includes at least one of an alkyl monophenol antioxidant, an alkyl polyphenol antioxidant, and a thiopolyphenol antioxidant.
[0016] Furthermore, the molecular structure of the alkyl monophenol antioxidant contains only one hindered phenol unit, and the ortho position of the phenolic hydroxyl group of the hindered phenol unit is usually connected to an alkyl substituent, such as a tert-butyl group, etc. Preferably, the alkyl monophenol antioxidant includes at least one of 2,6-di-tert-butyl-4-methylphenol (i.e., antioxidant 264).
[0017] Furthermore, the molecular structure of the alkyl polyphenol antioxidant contains two or more hindered phenol units, and these hindered phenol units may be connected by a specific bridge bond (such as a methylene group). At the same time, the phenolic hydroxyl group of the hindered phenol unit is also usually connected to an alkyl substituent. Preferably, the alkyl polyphenol antioxidant includes at least one of tetra-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (i.e., antioxidant 1010), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine (i.e., antioxidant 1098), and 2,2'-methylenebis(4-methyl-6-tert-butylphenol) (i.e., antioxidant 2246).
[0018] Specifically, the thiopolyphenol antioxidant is a special type of hindered phenol antioxidant, and its molecular structure not only contains hindered phenol units, but also introduces sulfur atoms as bridge bonds or substituents. Preferably, the thiopolyphenol antioxidant includes 4,4'-thiobis(6-tert-butyl-3-methylphenol (i.e., antioxidant 300).
[0019] Furthermore, the weight ratio of the amine antioxidant to the hindered phenol antioxidant is 1:(1-2). Within this ratio range, the two antioxidants can better exert their antioxidant properties and reduce their mobility in the composite material.
[0020] Preferably, the weight ratio of the amine antioxidant to the hindered phenol antioxidant is 1:(1.2-1.8).
[0021] Preferably, the density of the ethylene-1-octene block copolymer is 0.860 to 0.890 g / cm 3 .
[0022] More preferably, the density of the ethylene-1-octene block copolymer is 0.866 to 0.887 g / cm 3 .
[0023] Furthermore, the melt flow rate (MFR) of the polypropylene at 230°C and 2.16kg is 1.0-70g / 10min. When the melt flow rate of the polypropylene is within this range, the polypropylene composite material system has good fluidity, which is conducive to uniform mixing of the raw material components. The melt flow rate (MFR) of the polypropylene is measured according to the standard method of "ISO 1133-1:2011".
[0024] Specifically, in the present invention, the melt flow rate of the polypropylene can be 1.0 g / 10min, 2.5 g / 10min, 10 g / 10min, 15 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min, 35 g / 10min, 60 g / 10min, 70 g / 10min, etc., or an interval range formed by any of the above values, such as 1-5 g / 10min, 10-20 g / 10min, 25-35 g / 10min, etc., but is not limited thereto.
[0025] Preferably, the melt flow rate of the polypropylene at 230° C. and 2.16 kg is 2.5 to 60 g / 10 min.
[0026] More preferably, the melt flow rate of the polypropylene at 230° C. and 2.16 kg is 10 to 35 g / 10 min.
[0027] Preferably, the polypropylene is selected from at least one of homopolymer polypropylene, random copolymer polypropylene and block copolymer polypropylene.
[0028] Furthermore, in the present invention, the mass percentage of polypropylene in the low-emission polyolefin composite material is not less than 43%; preferably, the mass percentage of polypropylene in the low-emission polyolefin composite material is not less than 52%.
[0029] Preferably, a low-emission polyolefin composite material comprises the following components by weight: 72-82 parts of polypropylene, 18-27 parts of ethylene-1-octene block copolymer, 2-5 parts of compatibilizer, 0.2-0.8 parts of composite antioxidant, and 10-45 parts of filler.
[0030] More preferably, a low-emission polyolefin composite material comprises the following components by weight: 75-80 parts of polypropylene, 20-25 parts of ethylene-1-octene block copolymer, 3-4 parts of compatibilizer, 0.3-0.6 parts of composite antioxidant, and 20-35 parts of filler.
[0031] Furthermore, the filler includes at least one of talc, calcium carbonate, and basic magnesium sulfate whiskers.
[0032] The commonly used compatibilizers for polypropylene in the art can be used in the present invention, and the compatibilizer is preferably grafted modified polypropylene. The grafted polypropylene contains polypropylene segments, which can significantly improve its dispersibility in the polypropylene matrix.
[0033] Furthermore, the graft-modified polypropylene includes maleic anhydride grafted polypropylene or silane grafted polypropylene.
[0034] Furthermore, the maleic anhydride grafted polypropylene can be a commercially available product or a homemade raw material, and the homemade method is as follows: according to the ratio, polypropylene, maleic anhydride and peroxide (such as diisopropylbenzene peroxide, DCP) are extruded through a twin-screw extruder, and the screw temperature range is 165-200°C to obtain maleic anhydride grafted polypropylene.
[0035] Furthermore, the homemade method of the silane-grafted polypropylene is as follows: polypropylene, vinyl trichlorosilane and peroxide (such as DCP) are extruded through a twin-screw extruder according to the ratio, and the screw temperature range is 180-200° C. to obtain silane-grafted polypropylene.
[0036] Preferably, the grafting rate of the graft-modified polypropylene is 0.5-1 wt %, wherein the grafting rate is tested and calculated by acid-base titration method.
[0037] The grafted modified polypropylene is used as an auxiliary agent, and its content in the composition of the present invention is relatively low, so the technical solution of the present invention has no special requirements for other parameters of the grafted polypropylene.
[0038] The present invention also protects a method for preparing the low-emission polyolefin composite material, comprising the following steps:
[0039] The method is prepared by uniformly mixing polypropylene, ethylene-1-octene block copolymer, compatibilizer, composite antioxidant and filler and then melt-extruding the mixture.
[0040] Furthermore, the temperature of the melt extrusion is 160-220°C.
[0041] Preferably, the melt extrusion is carried out using a 75D co-rotating twin-screw extruder, and the temperatures from the feeding section to the die head of the twin-screw extruder are 170±10℃, 200±10℃, 200±10℃, 210±10℃, 210±10℃, 205±10℃, 205±10℃, 205±10℃, 200±10℃, and 200±10℃ respectively.
[0042] The present invention also protects the use of the low-emission polyolefin composite material in the preparation of automobile parts.
[0043] Compared with the prior art, the present invention has the following beneficial effects: by adding a specific combination of composite antioxidants and ethylene-1-octene block copolymers in a polypropylene matrix, the present invention can significantly improve the antioxidant performance of the obtained polyolefin composite material, reduce the emission of small molecule additives and aldehyde substances, and has good mechanical properties. On the one hand, the hard segment of the ethylene-1-octene block copolymer has a higher crystallization rate and a more regular crystal morphology, and can work together with the polypropylene matrix to obtain a stable crystalline network structure, hindering the precipitation of small molecule additives and oxidation products; on the other hand, the ethylene-1-octene block copolymer has good processing performance, and its soft segment has good compatibility with amine antioxidants, further reducing the precipitation of antioxidants, so that the composite antioxidant can play a good synergistic role, long-term guarantee The antioxidant performance of the polyolefin composite material, reduce the oxidative degradation of the polyolefin composite material from the root, and reduce the odor emission performance of the polyolefin composite material; and the obtained low-emission polyolefin composite material also has good mechanical properties. DETAILED DESCRIPTION
[0044] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0045] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0046] Examples and Comparative Examples Raw Materials Description:
[0047] Polypropylene:
[0048] PP-1: BX3500 (block copolymer, MFR = 10 g / 10 min at 230 ° C and 2.16 kg load), purchased from Aiskai, South Korea;
[0049] PP-2: BX3800 (block copolymer, MFR = 30 g / 10 min at 230 ° C and 2.16 kg load), purchased from Aiskai, South Korea;
[0050] PP-3: SZ30S (homopolymer polypropylene), MFR = 30 g / 10 min at 230 °C and 2.16 kg load), purchased from Sino-Korean Petrochemical (Wuhan);
[0051] PP-4: SM198 (copolymer polypropylene), MFR = 2.5 g / 10 min at 230 ° C and 2.16 kg load, purchased from Malaysia Datang;
[0052] PP-5: BX3900 (copolymer polypropylene), MFR = 60 g / 10 min at 230 ° C and 2.16 kg load, purchased from Aiskai, South Korea;
[0053] filler:
[0054] Filler-1: TYT-777A (3000 mesh talc), purchased from Liaoning Tianyuan;
[0055] Filler-2: calcium carbonate, 75T, purchased from Changxing Omiya;
[0056] Filler-3: WS-1S2 (basic magnesium sulfate whisker), purchased from Yingkou Kangru Technology;
[0057] Ethylene-1-octene block copolymer:
[0058] Ethylene-1-octene block copolymer OBC-1: DOW 9500, density 0.877 g / cm 3 , purchased from Dow Chemical;
[0059] Ethylene-1-octene block copolymer OBC-2: DOW 9107, density 0.866 g / cm 3 , purchased from Dow Chemical;
[0060] Ethylene-1-octene block copolymer OBC-3: DOW 9530, density 0.887 g / cm 3 , purchased from Dow Chemical;
[0061] Ethylene-octene random copolymer POE: 8200, purchased from Dow Chemical;
[0062] Compatibilizer:
[0063] Compatibilizer-1: maleic anhydride grafted polypropylene, the grafting rate of maleic anhydride is 0.8wt%, purchased from Jiayirongde CMG9801;
[0064] Compatibilizer-2: silane grafted polypropylene, the grafting rate of silane is 1wt%, and it is self-made. The self-made method is as follows: weigh 100 parts of polypropylene, 2 parts of vinyl trichlorosilane, and 0.15 parts of peroxide initiator DCP (diisopropylbenzene peroxide), use a twin-screw extruder for grafting reaction, the temperature is 180-200°C, and the rotation speed is 300RPM to prepare silane grafted polypropylene;
[0065] Among them, the grafting rate was tested and calculated by acid-base titration method;
[0066] Antioxidants:
[0067] Antioxidant-1: Octylated diphenylamine (an alkyl diphenylamine antioxidant), purchased from Jiangsu Feiya Chemical Group Co., Ltd.
[0068] Antioxidant-2: diphenylamine (belongs to the aromatic amine antioxidant), commercially available;
[0069] Antioxidant-3: Antioxidant 1010 (belongs to the alkyl polyphenol antioxidant), commercially available;
[0070] Antioxidant-4: Antioxidant 264 (belongs to the alkyl monophenol antioxidant), commercially available.
[0071] Antioxidant-5: Antioxidant 300 (belongs to the thiopolyphenol antioxidant), commercially available.
[0072] Antioxidant-6: Antioxidant 168 (a phosphite antioxidant), commercially available;
[0073] Unless otherwise specified, the components used in the parallel embodiments and comparative examples are all the same commercially available products.
[0074] Examples 1 to 17 A low-emission polyolefin composite material
[0075] This embodiment provides a low-emission polyolefin composite material, which is prepared according to the formula in Table 1 and a preparation method comprising the following steps:
[0076] According to the stated weight portions, polypropylene, ethylene-1-octene block copolymer, compatibilizer, composite antioxidant and filler are uniformly mixed and melt-extruded to obtain the product, wherein a 75D co-rotating twin-screw extruder is used for melt extrusion, and the temperatures from the feeding section to the die of the twin-screw extruder are 170°C, 200°C, 200°C, 210°C, 210°C, 205°C, 205°C, 205°C, 200°C and 200°C, respectively.
[0077] Comparative Examples 1 to 6 Polyolefin Composite Materials
[0078] The weight parts of the raw materials used in the following comparative examples are shown in Table 2.
[0079] Comparative Example 1 provides a polyolefin composite material, which is prepared by referring to the method of Example 1, and is different from Example 1 in that the composite antioxidant is replaced by an amine antioxidant of equal mass.
[0080] Comparative Example 2 provides a polyolefin composite material, which is prepared by referring to the method of Example 1, and is different from Example 1 in that the composite antioxidant is replaced by an equal mass of hindered phenol antioxidant.
[0081] Comparative Example 3 provides a polyolefin composite material, which is prepared by referring to the method of Example 1, and is different from Example 1 in that the hindered phenol antioxidant is replaced by an equal mass of a phosphite antioxidant.
[0082] Comparative Example 4 provides a polyolefin composite material, which is prepared by referring to the method of Example 1, and is different from Example 1 in that the amine antioxidant is replaced by an equal mass of a phosphite antioxidant.
[0083] Comparative Example 5 provides a polyolefin composite material, which is prepared by referring to the method of Example 1, and is different from Example 1 in that the composite antioxidant is replaced by an equal mass of a phosphite antioxidant.
[0084] Comparative Example 6 provides a polyolefin composite material, which is prepared by referring to the method of Example 1, and is different from Example 1 in that the ethylene-1-octene block copolymer is replaced by an ethylene-octene random copolymer POE of equal mass.
[0085] Table 1 Weight parts of raw materials used in Examples 1 to 17
[0086]
[0087]
[0088] Table 1
[0089] Components Example 10 Embodiment 11 Example 12 Example 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 PP-1 78 78 78 78 78 78 70 85 Filler-1 28 28 28 28 28 28 / / Filler-3 / / / / / / / 55 OBC-1 23 23 23 23 23 23 30 15 Compatibilizer-1 / 3.5 3.5 3.5 3.5 3.5 1 6 Compatibilizer-2 3.5 / / / / / / / Antioxidant-1 0.2 0.2 0.2 / / / 0.05 0.33 Antioxidant-2 / / / 0.2 0.2 0.2 / / Antioxidant-3 0.3 / / 0.3 / / 0.05 0.67 Antioxidant-4 / 0.3 / / 0.3 / / / Antioxidant-5 / / 0.3 / / 0.3 / /
[0090] Table 2 Weight parts of raw materials used in Comparative Examples 1 to 6
[0091] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 PP-1 78 78 78 78 78 78 Filler-1 28 28 28 28 28 28 OBC-1 23 23 23 23 23 / POE / / / / / 23 Compatibilizer-1 3.5 3.5 3.5 3.5 3.5 3.5 Antioxidant-1 0.5 / 0.2 / / 0.2 Antioxidant-3 / 0.5 / 0.2 / 0.3 Antioxidant-6 / / 0.3 0.3 0.5 /
[0092] Performance Testing
[0093] The properties of the polyolefin composite materials obtained in the above examples and comparative examples were characterized, and the specific test items, test methods and results are as follows:
[0094] The polyolefin composite materials prepared in the embodiment and the comparative example were tested according to the VW 50180-Vehicle In-Vehicle Volatile Control Standard Test, and the formaldehyde content, odor level, TVOC value, and tensile strength were tested according to the standard "ISO 527-1-2019". The sample size was 170 mm × 10 mm × 4 mm, and the tensile rate was 50 mm / min. The results are listed in Table 4 below.
[0095] Among them, the limit value of formaldehyde is clearly stipulated in the VW 50180 standard, which is generally ≤10mg / kg, which means that the air quality in the car meets health requirements;
[0096] The odor level standards are shown in Table 3. The limit of the odor level is generally ≤ Level 3, which means that the sample cannot emit obvious irritating or unpleasant odor during the test.
[0097] Table 3 Odor level standards
[0098] grade Grade Standard Level 1 No odor Level 2 Slight smell Level 3 Tasteful but not irritating Level 4 Has a pungent smell Level 5 Strong pungent smell Level 6 Unbearable taste
[0099] Table 4 Performance results of polyolefin composites
[0100]
[0101]
[0102] Note: ND: ND means not detected or below the detection limit.
[0103] From the above results, it can be seen that the results of Examples 1 to 5 show that the mechanical properties of the polypropylene composite materials prepared by using different polypropylene matrices are slightly different, but due to the addition of additives of specific composition, the influence on the emission performance of the prepared composite materials is small, and low emission can be maintained, which also shows that the above-mentioned additive combination of the present invention can be applied to the polypropylene matrix currently available on the market;
[0104] The results of Examples 1 and 6-7 show that the change of filler type has little effect on the low emission performance.
[0105] The results of Examples 1 and 8 to 9 show that ethylene-1-octene block copolymers (OBC) of different densities can be used in the present invention to prepare polypropylene composite materials with low emission performance.
[0106] The results of Example 1 and Example 10 show that polypropylenes grafted with different substances can be used as the compatibilizer of the present invention to prepare polypropylene composite materials with low emission performance.
[0107] The results of Example 1, Examples 11 to 15, and Comparative Examples 1 to 6 show that adding a specific combination of composite antioxidants and ethylene-1-octene block copolymers to the polypropylene matrix of the present invention can significantly improve the antioxidant properties of the composite material, reduce the emission of small molecule additives and aldehyde substances, and have good mechanical properties, with a tensile strength of ≥20Mpa. This is because the above-mentioned specific combination of composite antioxidants has good antioxidant properties in the polyolefin composite material system described in the present invention; in addition, on the one hand, the hard segment of the ethylene-1-octene block copolymer has a higher crystallization rate and a more regular crystal morphology, and can work together with the polypropylene matrix to obtain a stable crystalline network structure, hindering the precipitation of small molecule additives and oxidation products; on the other hand, the ethylene-1-octene block copolymer has good processing properties, and its soft segment has good compatibility with the amine antioxidant, further reducing the precipitation of the antioxidant, so that the composite antioxidant can play a good synergistic role, long-term guarantee The antioxidant performance of the polyolefin composite material, reduce the oxidative degradation of the polyolefin composite material from the root, and reduce the odor emission performance of the polyolefin composite material; and the resulting low-emission polyolefin composite material also has good mechanical properties.
[0108] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A low-emission polyolefin composite material, characterized in that: The invention comprises the following components by weight: 70 to 85 parts of polypropylene, 15 to 30 parts of ethylene-1-octene block copolymer, 1 to 6 parts of compatibilizer, 0.1 to 1 part of composite antioxidant and 0 to 55 parts of filler; wherein the composite antioxidant comprises amine antioxidant and hindered phenol antioxidant.
2. The low-emission polyolefin composite material according to claim 1, characterized in that: The amine antioxidant includes at least one of an aromatic amine antioxidant and an alkyl diphenylamine antioxidant.
3. The low-emission polyolefin composite material according to claim 1, characterized in that: The hindered phenol antioxidant includes at least one of an alkyl monophenol antioxidant, an alkyl polyphenol antioxidant, and a thiopolyphenol antioxidant.
4. The low-emission polyolefin composite material according to claim 1, characterized in that: The weight ratio of the amine antioxidant to the hindered phenol antioxidant is 1:(1-2).
5. The low-emission polyolefin composite material according to claim 1, characterized in that: The density of the ethylene-1-octene block copolymer is 0.860 to 0.890 g / cm 3 .
6. The low-emission polyolefin composite material according to claim 1, characterized in that: The melt flow rate of the polypropylene at 230° C. and 2.16 kg is 1 to 70 g / 10 min.
7. The low-emission polyolefin composite material according to claim 1, characterized in that: The filler includes at least one of talc, calcium carbonate, and basic magnesium sulfate whiskers.
8. The low-emission polyolefin composite material according to claim 1, characterized in that: The compatibilizer is graft-modified polypropylene.
9. The method for preparing the low-emission polyolefin composite material according to any one of claims 1 to 8, characterized in that: The steps include: The method is prepared by uniformly mixing polypropylene, ethylene-1-octene block copolymer, compatibilizer, composite antioxidant and filler and then melt-extruding the mixture.
10. Use of the low-emission polyolefin composite material according to any one of claims 1 to 8 in the preparation of automobile parts.